DIFFERENT FEATURES OF BUSCHKE-LÖWENSTEIN CARCINOMA - Waldemar Augusto Rivoire; Heleusa Monego; Marcia Appel; Ricardo dos Reis; Antônio Pütten; Edison Capp (Clinical and Biomedical Research, 2020)
Buschke-Löwenstein carcinomas are rare manifestations of condyloma acuminatum. This study presents two different clinical manifestations of Buschke-Löwenstein arcinoma. Correct diagnosis is a challenge. Despite the absence of histological signs of malignancy, malignant transformation into invasive squamous cell carcinoma may occur. Early and radical excision remains as the treatment of choice. Key words: Buschke-Löwenstein carcinoma; verrucous carcinoma; human papilloma virus; gynecological oncology